Establishing Normal Variances and Expectations for Quadriceps Limb Symmetry Index Benchmarks Based on Time from Surgery After Anterior Cruciate Ligament Reconstruction. - Sean Hazzard; Saoirse Connolly; Ashley Wiater; Isabella Sprague; Emily Doolan-Roy; Rachel Lampros; Peter D Asnis (North American Sports Medicine Institute, 2024)
The anticipated timeline for muscle strength as well as return to running and sports are some of the most common inquiries by patients undergoing anterior cruciate ligament reconstruction. Despite the popularity of this procedure, the answers to these inquiries are not well described in the literature. The purpose of this study was to evaluate the range of quadriceps strength percentage and function benchmarks at various points after anterior cruciate ligament reconstruction surgery based on sex, age, and graft. # Design Observational Cohort Study # Methods Patients who underwent anterior cruciate ligament reconstruction (ACLR) were evaluated at various points after their surgery with handheld dynamometer assessments. Additional hop and balance testing was performed and patients were evaluated for clearance for running and sport via a physical therapist directed functional movement assessment (FMA). The progression of quadriceps symmetry throughout the postoperative period was examined with multi-level models, estimates of time to reach 70%, 80%, and 90% quadriceps symmetry were obtained from the fitted model. # Results A total of 164 patients were evaluated. Patients either received bone-tendon-bone (BTB) autograft (n=118) or BTB allograft (n=46) for their ACL graft. Average age was 31.1 years-of-age (SD: 13.6). Males undergoing ACLR using BTB autograft (n=53) were able to achieve 80% quadriceps symmetry earlier than females (n=65) (5.7 months vs 7.1 months), were cleared to return to run sooner (5.6 months vs 6.8 months) and passed an FMA exam earlier (8.5 months vs 10 months). Males undergoing ACLR with allograft (n=13) were able to achieve 80% quadriceps symmetry earlier than females (n=33) (3.9 months vs 5.4 months) and were cleared to run sooner (4.5 months vs 5.8 months). # Conclusion Patients undergoing BTB autograft obtain 80% quadriceps symmetry at an average of 5.7 months for males and 7.1 months for females. Individuals under the age of 25 obtain their quadriceps symmetry faster and are cleared to return to running faster than individuals over 25. Male sex is associated with decreased amount of time to obtain clearance for running and for full activity. Male sex is associated with decreased amount of time to regain quadriceps symmetry however this was not significant. # Level of Evidence 4 (Case series)